SOCIAL MANAGEMENT STRATEGY - Sayfullayevich , Mansurov Abdulla (PT. Antis International Publisher, 2024)
The article explores the concept of social management strategy, which involves structured approaches to addressing social challenges and promoting social welfare. It highlights the essential components of these strategies, including vision setting, stakeholder engagement, policy development, resource allocation, and community participation. The article also differentiates between government-led, corporate (CSR), and NGO-driven strategies, discussing their unique roles in fostering societal improvement. Furthermore, the challenges of implementing social management strategies—such as resource limitations, political instability, and data constraints—are examined. Overall, it emphasizes the importance of sustainable, data-driven strategies in achieving long-term social development.